Decentered Individualized Sphero-Cylindrical (DISC) Ablation and Corneal Crosslinking in Patient with Progressive Keratoconus - Igor Knezović; Sara Djurić (Case Reports in Ophthalmological Medicine)
Aim. To report a new method with which we have treated a 29-year-old patient with keratoconus and progressive bilateral visual loss during the past few years. Methods. The patient underwent inferotemporal decentered individualized sphero-cylindrical (DISC) ablation and crosslinking (CXL) of the left eye. After administration of topical anesthetic, the patient was subjected to phototherapeutic keratectomy (PTK) laser ablation of the central 7.0 mm optical zone with 50 μm depth of epithelial ablation. To avoid the possible outcome of corneal haze, 0.02% mitomycin C (MMC) was applied to the stromal surface for 40 seconds. Riboflavin 0.1% solution was then administered topically every 2 minutes for a 30-minute period followed by 5 cycles of corneal crosslinking, radiating with UV-A at 3 mW/cm2, for a duration of 5 minutes. Results. 17 months postoperative, there was an impressive improvement in uncorrected distance visual acuity, and the cornea became more regular. Results of Fourier’s analysis imply a drop of irregularity (-28.6% two months and –63% seventeen months postoperative), Zernike analysis revealed a decrease of higher order aberrations (spheric and comatic aberrations), and corneal index values in the 8 mm zone (IHD, ISV, and IVA) became lower, compared to the preoperative values. Conclusion. It is possible to obtain better outcome of visual function with DISC ablation through an individual approach compared to CXL solely. This approach might be a promising strategy in retrieving impaired vision in patients suffering from keratoconus.